2021
DOI: 10.1016/j.ebiom.2021.103276
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel myelin repair drugs by modulation of oligodendroglial differentiation competence

Abstract: Background In multiple sclerosis loss of myelin and oligodendrocytes impairs saltatory signal transduction and leads to neuronal loss and functional deficits. Limited capacity of oligodendroglial precursor cells to differentiate into mature cells is the main reason for inefficient myelin repair in the central nervous system. Drug repurposing constitutes a powerful approach for identification of pharmacological compounds promoting this process. Methods A phenotypic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…Several recent studies have focused on the effects of commonly prescribed antipsychotic drugs on oligodendrocytes/myelin[ 184 ]. However, testing the effects of novel compounds intended to induce oligodendrogenesis and (re)myelination[ 116 ] in preclinical models of schizophrenia and bipolar disorder could also hold great promise for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have focused on the effects of commonly prescribed antipsychotic drugs on oligodendrocytes/myelin[ 184 ]. However, testing the effects of novel compounds intended to induce oligodendrogenesis and (re)myelination[ 116 ] in preclinical models of schizophrenia and bipolar disorder could also hold great promise for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of that work, Katsel et al [ 113 ] suggested that postmitotic oligodendrocytes may abnormally re-enter the cell cycle, while a significantly increased level of NG2 in the putamen of schizophrenia patients suggested that OPCs failed to exit the cell cycle. Dysregulation of p57Kip2 gene expression in schizophrenia patient samples[ 113 ] could also be related to impaired oligodendrocyte maturation, since this protein has been characterized as an oligodendroglial differentiation competence marker[ 114 - 116 ].…”
Section: Comparison Of Altered Features Of Oligodendrocytes and Myeli...mentioning
confidence: 99%
“…Manousi et al ( Manousi et al, 2021 ) identified some new small molecules that could promote oligodendrocyte differentiation, even in the presence of the oligodendrocyte differentiation inhibitor p57Kip2 and found subsets that could promote human oligodendrocyte genesis and myelin formation in vitro . Among them, danazol and parbendazole promote oligodendrocyte differentiation and myelin repair.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput screening (HTS) platform allows for the identification of approved compounds for repurposing therapy as well as drug discovery ( Eleuteri et al, 2017 ; Manousi et al, 2021 ). Indeed, screenings for pharmaceutical compounds that promote myelination have revealed several modulators for G protein-coupled receptor (GPCRs) that are major pharmacological targets for myelin-related diseases ( Table 3 ; Mei et al, 2016 ; Mogha et al, 2016 ; Folts et al, 2019 ).…”
Section: Enhancing Oligodendrocytes Myelination As Therapeutic Strategies Against White Matter Injurymentioning
confidence: 99%